Converting the Function of Rubber Plantation Land to Housing in Way Kanan, Lampung (Field Study at Transmedika Residence, Way Tuba District) - Benny Djaja; Altina Intan N (Sociological Jurisprudence Journal, 2023)
The purpose of this writing is to analyze regarding the factors that cause the conversion of plantation land into housing and the impact of land conversion plantation into housing in Way Tuba District. The research method uses qualitative research. Factors causing land use change plantation into housing the internal factors of the plantation owner taking into account the social and environmental conditions of the local residents and land use. The internal factor of the garden owner is expected to be the way for the growth and development of the area and local people. If a factor can affect a human action, it is hoped that this factor will have benefits in it by taking into account the surrounding conditions and getting benefits for all parties and there is no loss in it. It is hoped that Internal and external factors such as the surrounding environment will not conflict with laws and regulations and remain steadfast in the 1945 Constitution that everything must aim at the welfare of all Indonesian people. This research aims to discuss about converting the function of rubber plantation land to housing in way Kannan, Lampung. The method used in this research is method qualitative. The positive impact that is felt is the emergence of new residential areas to meet housing needs, increased trading activities and additional Regional Original Income (PAD) from levies and taxes, while the negative impact of converting plantation land into settlements is that food productivity will decrease or decrease. Plantation land, which has become narrower due to conversion of functions, has also resulted in a decrease in food production.